Exogenous putrescine enhances lime stress tolerance in grapevine rootstock-scion combinations - Selda Daler; Ozkan Kaya; Tugba Kılıç; Hanifeh Seyed Hajizadeh; Hasan Bay; Fadime Ates; Turhan Yilmaz; Harlene Hatterman-Valenti (BMC Plant Biology)
Abstract Background Climate change and drought are increasing soil lime content globally, a major threat to crop productivity and quality, especially for viticulture. High lime concentrations disrupt nutrient uptake, leading to chlorosis and reduced growth in plants. While exogenous putrescine applications have shown potential in enhancing plant defense responses against various environmental stresses, their efficacy in modulating lime stress has not been previously explored. In this regard, we studied the effects of putrescine on grapevine saplings under varying lime conditions. The experiment used the Karaerik grape variety, an economically important indigenous cultivar from Eastern Black Sea Region of Turkey, grafted onto three American rootstocks with different lime tolerances: Fercal (high), 5 BB (moderate), and 3309 C (low). These were tested under four lime levels (0%, 20%, 40%, and 60% CaO) and treated with different putrescine concentrations (0, 0.05, 0.1, and 0.2 mM) to examine their morphological, biochemical, and physiological responses under lime stress conditions. Results The results indicated that lime stress adversely affected the growth and development of grapevine saplings by reducing growth parameters, SPAD index, stomatal conductance, and relative water content (RWC), while increasing membrane damage and malondialdehyde (MDA) content. However, different rootstock/cultivar combinations exhibited distinct strategies to cope with lime stress. The highly tolerant Fercal/KE combination maintained higher chlorophyll content, better RWC, and stomatal conductance, supported by increased production of protective enzymes, along with higher proline and protein accumulation, ultimately leading to improved growth and development under lime stress. Exogenous putrescine applications effectively improved plant performance across all rootstock/cultivar combinations, with different concentrations showing optimal results for each combination. The 0.2 mM putrescine treatment significantly enhanced growth parameters, chlorophyll content, stomatal conductance, RWC, and protective enzyme levels while reducing membrane damage and lipid peroxidation in 3309 C/KE combination, which typically shows low lime tolerance. For the moderately tolerant 5 BB/KE, 0.1 mM putrescine was most effective, while the already lime-tolerant Fercal/KE responded best to 0.05 mM putrescine applications. These optimized concentrations demonstrated that putrescine can effectively enhance lime stress tolerance, particularly in more sensitive rootstock/cultivar combinations. Conclusion This study demonstrated that exogenous putrescine applications effectively mitigated lime stress effects in grapevine saplings by improving physiological parameters and reducing oxidative damage, with optimal concentrations varying according to rootstock tolerance levels (0.2 mM for 3309 C/KE, 0.1 mM for 5 BB/KE, and 0.05 mM for Fercal/KE). The findings revealed that putrescine’s protective effects were most pronounced in lime-sensitive rootstock combinations, suggesting its potential as a protective compound for improving lime stress tolerance in grapevine cultivation.